Into the (Gendered) Blue: New Perspectives on Gender Equality and Participation in Blue Growth - Magnus Boström; Kristina Svels; Milena Arias Schreiber (Ocean and Society)
In the context of the global adoption of the blue economy agenda, new challenges and opportunities emerge for gender mainstreaming in traditional male‐dominated maritime industries. This thematic issue mobilizes knowledge on barriers and structural hindrances faced by women in the blue economy, from exclusionary workplace norms and hierarchies to inadequate support for work–life balance. These hindrances discourage women’s entry and retention in industries like fisheries, aquaculture, maritime transportation, and marine research. Lessons from the Nordic countries, which have significantly advanced gender equality and adopted numerous policies to enhance gender inclusivity, show that in the absence of effective implementation and evaluation of policy impacts, policies alone are not effective. Using gender as an analytical perspective reveals the importance of language and discourses in advancing gender inclusion, highlights issues of intersectionality across national borders, and exposes the need for blue justice alongside blue economy agendas. The collection of articles underscores the need for both systemic change and localized, tailored interventions. The methodological contribution exemplifies how discourse analysis unpacks societal norms, while ethnography reveals on‐the‐ground experiences of exclusion and resistance. Furthermore, tracking career trajectories provides data‐driven insights into workforce retention, while interviews analyze the nuanced motivations and challenges women face. It is concluded that the agendas of the blue economy and gender equality could be indeed compatible, however, it must be acknowledged that the way these two can be simultaneously pursued remains a challenge that needs action.